2012
DOI: 10.21897/rmvz.216
|View full text |Cite
|
Sign up to set email alerts
|

Identificación de agentes infecciosos asociados con Diarrea Neonatal Bovina en la Sabana de Bogotá

Abstract: RESUMENObjetivo. Determinar los agentes infecciosos asociados causalmente a la presentación de Diarrea Neonatal Bovina (DNB) en terneros menores de 5 semanas de vida, procedentes de fincas lecheras y de producción mixta de la Sabana de Bogotá. Materiales y métodos. Se seleccionaron por conveniencia 21 fincas, se realizó seguimiento de 620 terneros desde el nacimiento hasta las 5 semanas de edad, se tomaron muestras de materia fecal de los animales que presentaron cuadro clínico de diarrea y de terneros clínica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
1
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 16 publications
2
1
0
2
Order By: Relevance
“…and Rotavirus were the agents with the highest prevalence (53.3% and 46.7%, respectively), which could explain the high prevalence in mixed infections. This result is consistent with those reported in other studies (Pardo and Oliver 2012;Içen et al, 2013;Gillhuber et al, 2014). Cryptosporidium spp.…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…and Rotavirus were the agents with the highest prevalence (53.3% and 46.7%, respectively), which could explain the high prevalence in mixed infections. This result is consistent with those reported in other studies (Pardo and Oliver 2012;Içen et al, 2013;Gillhuber et al, 2014). Cryptosporidium spp.…”
Section: Resultssupporting
confidence: 94%
“…and Rotavirus the most common and E. coli (K99) the least common (P<0.05; Table 1). Similar prevalences have been observed with 93% (Içen et al, 2013) and 86% (Pardo and Oliver, 2012), this highlights the role that such etiopathogens exert upon most diarrhea cases in calves under intensive dairy production systems. Bartels et al (2010) reported that in 28.1% of the studied samples, no pathogens were detected, while in our study, no pathogens were detected only in 11 samples (12.2%).…”
Section: Resultssupporting
confidence: 86%
“…In Colombia, the prevalence of bovine rotavirus as a causal agent of BND development 13 , as well as the circulation of the G6 genotype 14 have been reported. The objective of this study was to characterize rotaviruses affecting calves in the Sabana region of Bogotá, Colombia, by viral genome detection and gene fragment sequencing, in order to determine homology with bovine rotaviruses isolated from Latin America and worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…Para 2012 se reporta una prevalencia del 5% en terneros de razas lecheras, en la zona noroccidental de la sabana de Bogotá (33). Para ese mismo año, se publica una seroprevalencia de 38,5% Cryptosporidium en terneros neonatos de la sabana de Bogotá (34).…”
Section: -Animalesunclassified